Karakterizacija hitro strjene evtektične zlitine Al-Si - Hertl, Bojan (Kovine zlitine tehnologije, 1999)
Rapid solidification processing is the way to achieve great microstructural refinement. The water atomisation technique has been used to produce rapidly solidified AlSi12 powders. Due to influence of rapid solidification on the eutectic particles the type of the oxyde layers and the microstructure after different cooling rates were observed. The thickness of the oxyde layers was evaluated by Auger Electron Spectroscopy (AES). The type of the oxyde was determined by X-Ray Diffraction method (XRD). Scanning Electron Microscopy (SEM) was used for morphological and microstructural observations.
Keywords: zlitine; prahovi; atomizacija